Evaluating the Efficacy of Platelet-Rich Plasma (PRP) in Accelerating Healing and Reducing Complications in Oral Surgery - Liza Mohanty; Abhishek Harish; Sachin B. Mangalekar; Ankur Jethlia; Honey Lunkad; Jessica Y. Jeevitha; Ramanpal S. Makkad (Wolters Kluwer Medknow Publications, 2024)
Background: The process of curing and regaining the integrity of damaged tissues is known as healing. An autologous concentration of platelets embedded in plasma is known as platelet-rich plasma (PRP). Aim: This study was conducted to evaluate the role of PRP in the fast healing of wounds and complications in oral surgical procedures. Materials and Methods: A total of 60 patients who underwent different oral surgical procedures were included in this study. PRP was placed in the surgical area after surgical procedures and recalled at the 2nd, 4th, and 6th month postoperatively. There was the assessment of soft tissue healing by measuring the probing depth in teeth adjacent to the surgical area and hard tissue healing in the form of alveolar bone density and alveolar bone height. The assessment of postoperative complications was also conducted. Results: The decrease in the probing depth at different follow-ups was greater in PRP patients showing better and fast soft tissue healing. The increase in alveolar height and alveolar bone density at different follow-ups was greater in the PRP group showing better and fast hard tissue healing. The frequency of complications, such as trismus and pain, was lesser in patients with PRP. Conclusion: The wound healing was at increased rate with reduced complications on using PRP in oral surgical procedures.